QUANTIFYING OPTIMAL POLICY IN AN ENDOGENOUS MODEL: A THEORETICAL ANALYSIS - Ahmed Bellakhdhar (Сучасний стан наукових досліджень та технологій в промисловості)
The subject matter of research is the examination of the optimal public policy in an R&D-based endogenous growth model with monopolistic supply of intermediate goods. The goal of the work is to study whether an adequate government intervention can provide the required incentives to correct market inefficiencies and make the decentralized economy to replicate the optimal solutions attainable by a social planner. The article solves the following tasks: finding the model economy’s decentralized equilibrium and social optimal solution, comparison of the welfare effects of different fiscal variables, consideration of the different market distortions and the choice of the appropriate policy variables that allow the decentralized economy to achieve sustainable optimal growth. Methods of mathematical formulation, theoretical analysis and economic interpretations have been used.  The following results were obtained: the first-best optimum can be decentralized by means of a tax on capital income at a constant rate combined with equality between the share of public spending in the total expenditure on education and the tax on labor income and a time-varying subsidy to R&D. Conclusions. Investments in knowledge-capital are the principal determinants of economic development. Our model incorporates three sources of inefficiency: monopolistic competition in the intermediate-goods sector, duplication externalities and spillovers in R&D. To correct these imperfections and achieve sustainable optimal growth, the intervention of the state by an effective fiscal policy is necessary.